Die belang van giste tydens weifermentasie - Lamprecht, Albertha (University of the Free State, 1997)
English: Cheese processed by traditional or modern methods inevitably produces large quantities of whey (approximately 84% of the volume of milk used). The disposal of whey is becoming a major industrial and environmental health problem and is difficult to separate from cheese technology. However, since a greater appreciation of the inherent nutritional value of whey constituents for both humans and livestock has become apparent, various new research projects have been initiated. In the light of growing global food shortages, the most logical use of whey would be to return it, in a palatable form, to the human food chain. The high salt content, low energy ratio and sweetening power of lactose, however, place constraints in the way of developing whey-derived food products. Single-cell protein, using deproteinized whey offer attractive new possibilities, not only from the standpoint of the current exhaustion of protein sources, but also because such food products have great potential for acceptance. The use of deproteinized whey offers attractive financial opportunities for the dairy industry by providing good quality whey protein on the one hand and by further processing of the deproteinized whey on the other. This can lead to even greater economic advantages if the deproteinized whey is enriched by means of suitable yeast strains to enhance the single-cell protein content. This protein enriched whey can primarily be applied for stockfeed with the envisaged development of a whey based food product for human consumption later. Fourteen lactose utilizing yeast strains, capable of fermenting lactose and producing high protein contents when grown on whey, were isolated from whey and its immediate environment. Priority selection studies were performed by growing each strain on whey, obtained during the processing of Cheddar cheeses, while monitoring their fermentative abilities, protein production capacity and the depletion of lactose. Based on these results, a yeast species namely Kluyveromyces marxianus var. lactis were selected for detailed fermentation studies. The yeast species were used for producing a wheyfermented product with high single-cell protein but low alcohol content. High levels. of protein 1.18 mg/ml were obtained in a 22 h fermentation period without any enrichment which reflects well on the possibility of implementing the system in the dairy industry.

Afrikaans: Kaas geprosesseer deur tradisionele en moderne metodes produseer 'n groot hoeveelheid wei, nagenoeg 84% van die volume van melk gebruik tydens kaasprosessering. Die storting van wei verskaf tans besoedelings probleme van groot omvang. Bewuswording van die voedingswaarde van wei vir beide menslike en dierlike gebruik het gelei tot talle nuwe navorsingprojekte. In die lig van die huidige voedseltekorte veral proteïen, bied die omskakeling van wei na bruikbare produkte soos enkelselproteïen-produkte 'n baie goeie alternatief. Die hoë soutkonsentrasie, lae energieverhouding en lae soetheid van laktose, plaas 'n demper op die ontwikkeling van nuwe weiprodukte. Die gebruik van gedeproteïeniseerde weipermeaat verskaf goeie finansiële vooruitsigte aan die suiwelbedryf deur die verskaffing van hoë kwaliteit weiproteïen aan die een kant en die benutting van gedeproteïeniseerde wei of permeaat aan die ander kant. Dit kan lei tot nog groter ekonomiese voordele indien 'n geskikte gisstam gevind kan word om sodoende die proteïen inhoud daarvan te verhoog. Hierdie proteïen verrykte weipermeaat kan aangewend word as veevoer met die oog op die ontwikkeling van 'n voedselproduk vir menslike gebruik in die toekoms. Veertien verskillende laktose benuttende gisstamme, wat in staat is om proteïen te produseer vanaf wei, is geisoleer vanaf 'n kaasfabriek en -fabrieksomgewing. 'n Seleksieprosedure is uitgevoer waartydens elke stam in gepasteuriseerde wei verkry tydens Cheddar kaasvervaardiging, geinokuleer is en hul fermenterende eienskappe asook proteïen produksie en uitputting van laktose gemonitor is. Gebaseer op hierdie resultate is 'n gisspesie naamlik Kluyveromyces marxianus var. lactis geselekteer vir verdere fermentasie studies. Hierdie gisspesie is gebruik om 'n gefermenteerde weiproduk met 'n hoë enkelselproteïen konsentrasie te produseer. 'n Hoë konsentrasie van proteïen naamlik 1.18 mg/ml is verkry tydens 'n fermentasieperiode van 22 uur sonder enige byvoegings tot perrneaat, wat 'n aanduiding is dat so 'n sisteem wel in die suiwelbedryf geïmplementeer kan word.
Keywords: Yeasts; Dairy processing; Whey -- Fermentation; Yeast fungi; Dissertation (M.Sc.Agric. (Food Science))--University of the Free State, 1997